TRADISI KHANDURI LAOT DALAM KEYAKINAN MASYARAKAT DESA LAMPULO KECAMATAN KUTA ALAM KOTA BANDA ACEH - Zila, Yuna; Yulianti, Fitriani; Zulfina, Oriza (Universitas Syiah Kuala, 2025)
Tradition is a culture that has been passed down from generation to generation from ancient ancestors to the present. Khanduri Laot is a tradition that has been carried out for a long time and continues to be a routine activity of the life of the people of Banda Aceh, to be precise in the village of Lampulo which is on the coast. Therefore, researchers want to know the implementation of the Khanduri Laot tradition in Kuta Alam sub-district and the people's belief in Khanduri Laot, as well as the benefits of the Khanduri Laot tradition for the Lampulo community. This research is qualitative based on descriptive research, using interview data collection techniques, observation and documentation. Data analysis techniques in this study are data reduction, data presentation, and conclusion/data verification. The results of the study show that the implementation of marine content begins with joint deliberations and the belief of the people of the village of Lampulo in Khanduri Laot is in principle still based on the teachings of Islamic law. According to the people of Lampulo, khanduri laot is held solely to obtain the pleasure and blessings of Allah SWT, because sustenance and safety come only from Allah SWT. For the people of Lampulo, Khanduri Laot is a manifestation of the relationship between humans as creatures of His creation and also the surrounding environment in dealing with the local environment and as a form of gratitude to Allah SWT who has provided sustenance, blessings and safety so far. actually the livelihood of the people of Lampulo is not determined by the existence of khanduri laot but that is just a coincidence. Indeed, the community said that in terms of experience and the impact on their fishing when carrying out Khanduri Laot compared to not implementing Khanduri Laot.